Hubungan Antara Self Compassion Dan Peer Group Influence Dengan Subjective Well-Being Pada Mahasiswa Yang Mengikuti Pembelajaran Daring - Setiani, Mefta; Malay, Mohammad Nursalim; Fitriani, Annisa; Tajuddin, Nilawati (Universitas Islam Negeri Raden Intan Lampung, 2022)
The latest policy in the world of education regarding teaching and learning activities that switched to using the online system since the covid-19 pandemic, become a challenge for various groups, including students. Previously research found the relationship and the role of self-compassion for subjective well-being in students but not yet been research in-depth related to subjective well-being in students who are undergoing online learning and there is not much-related research on the role of the independent variable peer group influence on subjective well-being on students. The purpose of this study is to analyze the relationship between self-compassion and peer group influence on the subjective well-being of students who take online learning.This research was conducted on 135 respondents from the Faculty of Ushuluddin and Religious Studies at UIN Raden Intan Lampung. Method data collection used in this study using the SWLS (Satisfaction with Life Scale) scale of 13 items (á = 0.844) and the PANAS scale (Positive and Negative Affect Schedule) as many as 13 items (á = 0.937) to measure the level of subjective well-being, and a self-compassion scale of 17 items (á = 0.909) and the peer group influence scale of 8 items (á = 0.779). The analysis technique used is multiple regression analysis with JASP software help vers.15.The results of the data analysis show:1. The results of hypothesis testing with an R-value of 0.647 and an R Square of 0.419, which means the variance of the capable subjective well-being explained by self-compassion and peer group influence is 0.419 or a percentage of 41.9% while the rest explained by other things not examined in the study.2. The results of the correlation test of the self-compassion variable with the Pearson value correlation 0.602 p < 0.001 which means partially self. variable compassion has a relationship with subjective well-being.3. The test results on the independent variable peer group influence found the value of Pearson correlation 0.392 p < 0.001, this means partially variable peer group influence has a relationship with subjective well-being. Keywords: Peer Group Influence, Self Compassion, Subjective Well-Being